1986
DOI: 10.1111/j.0954-6820.1986.tb02775.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function after Surgical Treatment of Nontoxic Goitre: A Randomized Study of Postoperative Thyroxine Administration

Abstract: Following thyroid resection for nontoxic goitre, 29 euthyroid patients were randomly allocated to no medication or to 0.2 mg levothyroxine daily (17 and 12 patients). The two groups were comparable in age, sex, extent of surgery and thyroid pathology. The patients were free from other endocrine disorders and had no other medication. Serum TSH, T4 and T3 were measured and T3‐resin test performed preoperatively and 14 days and 3, 6, 12 and 18 months postoperatively. All values were within normal range. Only at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…2), and to a lesser degree in nonendemic areas [6,48]. Since most of these goiters grow by mechanisms other than increased thyrotropin (TSH) stimulation, treatment with suppressive doses of thyroid hormones is usually doomed to failure and is not recommended [34,[90][91][92][93].…”
Section: Goiter In Iodine-sufficient Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…2), and to a lesser degree in nonendemic areas [6,48]. Since most of these goiters grow by mechanisms other than increased thyrotropin (TSH) stimulation, treatment with suppressive doses of thyroid hormones is usually doomed to failure and is not recommended [34,[90][91][92][93].…”
Section: Goiter In Iodine-sufficient Areasmentioning
confidence: 99%
“…Furthermore, L-thyroxine administration can induce thyrotoxicosis in "simple" goiters which are already autonomous or non-TSH dependent [57,58,91,95]. Similarly, most studies agree that routine L-thyroxine treatment following surgery is of no value [57,58,92,[96][97][98]. Thus, L-thyroxine substitution therapy should be restricted to goitrous patients with concomitant hypothyroidism and for those developing this condition following surgery [57,58,91,93].…”
Section: Goiter In Iodine-sufficient Areasmentioning
confidence: 99%
“…This high probability of goiter recurrence after subtotal thyroidectomy resulted in a preventive use of LT4. However, only one ( 30 ) out of four randomized trials ( 27 , 30 – 32 ) has demonstrated LT4 to be effective in this setting.…”
Section: Surgerymentioning
confidence: 99%
“…Numerous studies have demonstrated that about two-thirds of thyroid goiters decrease in size in response to treatment with thyroid hormone [2,3]. Some thyroid carcinomas also decrease in size in response to treatment with thyroid hormone [4][5][6], and recurrent thyroid cancer is less common [7] and survival appears to be better in patients receiving thyroid hormone [8]. Increasing serum TSH levels is also the best way to increase serum thyroglobulin levels in patients with residual thyroid cancer [9].…”
Section: Invited Commentarymentioning
confidence: 99%